Pengaruh Model Inkuiri Terbimbing Berbantuan Media PhET terhadap kemampuan berpikir kritis Peserta Didik - Siti Rahayu Fitriani; Aris Doyan; Muhammad Taufik; Wahyudi Wahyudi (Jurnal Penelitian Pendidikan IPA, 2024)
The purpose of this study was to examine the effect of guided inquiry learning in the use of PhET media on students' critical thinking skills. This study used quasi-experimental methods, group design for pretest and posttest. The independent variable in this study is the PhET media-assisted guided inquiry model used in the experimental class, while the control variable is the critical thinking ability of students. The study population consisted of all students who were in science class XI at SMAN 1 Pringgasela. The experimental group was selected from class XI IPA 2, while the control group was selected from class XI IPA 3. The mean value of the experimental group was determined at 37.54, in contrast to the average value of the control group of 39.36. Following the treatment, the average score of the experimental group exhibited a rise from 67.18 to 72.36, in contrast to the control group. The t test in this study showed a total value below the significant value of 0.050, indicating a value of 0.045. The application of the guided inquiry learning approach, in conjunction with the integration of media, has an apparent effect on developing and improving students' critical thinking abilities